Potential risks to the National Health Service (NHS) of a Post-Brexit US Trade Deal - Louise Dalingwater (Revue LISA)
At the very heart of the pro-Brexit narrative, currently supported by Eurosceptic politicians such as Boris Johnson, Michael Gove and David Davis, and Conservative think tanks including the Institute of Economic Affairs and Adam Smith’s Institute, is the belief that breaking European ties will enable Britain to reunite with the Anglosphere and notably its treasured ally, the United States. There are many indications that a post Brexit trade deal is in the pipeline with Donald Trump’s declaration in July 2019 that a “very substantial” trade deal was underway. Moreover, in late November 2019, Jeremy Corbyn contended that Conservatives were negotiating a secret trade deal containing clauses which would open the NHS up to American pharmaceutical companies. The central focus of this paper is thus to examine the likely consequences of a post-Brexit trade deal between the US and the UK and to consider to what extent it could undermine the UK’s ability to provide a free, universal public health service. In particular, it will examine empirical evidence on the impacts that FTAs have already had on access to medicine for countries which have been signatory to bilateral and plurilateral trade deals. Particular country contexts of price regimes for medication will be reviewed. It will also consider other FTA clauses such as public procurement and Investor State Dispute Settlement (ISDS) and their potential to disrupt national governments’ ability to protect public health service provision. Such evidence can then be used to hypothesise about the potential risks for Britain post Brexit.